A COMPARATIVE STUDY OF EDUCATORS’ VIEWS ON ADVANTAGES AND DISADVANTAGES OF OPEN EDUCATIONAL RESOURCES IN HIGHER EDUCATION - Melnikova, Julija; Zaščerinska, Jeļena; Ahrens, Andreas; Hariharan, Ramar; Clipa, Otilia; Sowinska-Milewska, Daria; Andreeva, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The aim of the contribution is to analyze advantages and disadvantages of open educational resources (OER) in higher education underpinning elaboration of a new research question. Comparative study was applied. The study was carried out in February 2016. Data was collected via semi-structured interviews. The sample included seven educators from different countries. The data were processed via structuring and summarizing content analysis. The respondents’ views are homogeneous. A new research question is formulated. Directions of further research are proposed.